1982
DOI: 10.1007/bf02289835
|View full text |Cite
|
Sign up to set email alerts
|

Die Schlei, ein Modell für die Verbreitung der StrandkrabbeCarcinus maenas

Abstract: ABSTRACT:The Schlei as a model for the distribution of the green shore crab Carcinus maenas. A Carcinus maenas population inhabiting the Schlei, a glacial fjord of the Baltic Sea, was studied during a three-year period of at least monthly sampling. Due to slightly higher water temperatures in the Schlei (c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 4 publications
(6 reference statements)
0
17
0
Order By: Relevance
“…However, the bucket trap data indicate that a significant proportion of the juvenile shore crabs participates in the tidal migration and stays in the subtidal waters during the preceding winter. The suppressed feeding of shore crabs in water temperatures below 7 ~ (Ropes, 1968) and their reduced activity during the winter months (Dries & Adelung, 1982) may decrease the predation pressure on juveniles, thereby allowing the coexistence of juvenile and .adult shore crabs in subtidal waters (Fig. 6).…”
Section: August / ~Cz~ Maymentioning
confidence: 99%
“…However, the bucket trap data indicate that a significant proportion of the juvenile shore crabs participates in the tidal migration and stays in the subtidal waters during the preceding winter. The suppressed feeding of shore crabs in water temperatures below 7 ~ (Ropes, 1968) and their reduced activity during the winter months (Dries & Adelung, 1982) may decrease the predation pressure on juveniles, thereby allowing the coexistence of juvenile and .adult shore crabs in subtidal waters (Fig. 6).…”
Section: August / ~Cz~ Maymentioning
confidence: 99%
“…This species has a wide temperature (0-33°C) and salinity (4-54) tolerance (Broekhuysen 1937;Naylor 1962;Crothers 1967;Rasmussen 1973;Dries and Adelung 1982;Behrens Yamada 2001), which varies between different life history stages, increasing with age. C. maenas occupy a variety of substrates (mud, sand, rock, eelgrass) and depths ranging from high tide to 6 m, although there have been records up to 60 m (Crothers 1968).…”
Section: Introductionmentioning
confidence: 99%
“…The lower temperature limit for feeding is generally considered to be 7°C [29], although Ropes [65] concludes that at temperatures as low as 7°C crabs from Massachusetts do not suppress feeding but activity and presumably feeding probably cease at some temperature below 7°C. In most populations, adult crabs migrate offshore when the water temperature drops below 8°C in winter and then return as the water warms in the spring [1,82,87,[103][104][105][106][107][108][109][110]. Audet et al [111] report that C. maenas in Prince Edward Island waters may feed at temperatures below 6°C but only in the fall, not in the spring, and Eriksson et al [63] indicates that feeding may occur below 7°C but almost ceases below 3-4°C for crabs in Sweden.…”
Section: Temperaturementioning
confidence: 99%
“…A linear regression analyzing male maximum carapace width and the latitude of each sample site in the native range found that latitude explained 61% of the variation in CW [23]. Within the native range in Europe, crabs generally do not exceed 86 mm but a single male with a carapace width of 100 mm was collected in western Sweden [105] and a 92 mm male crab from Denmark was reported by Eriksson & Edlund [62]. The smallest maximum CW male within a population (71 mm) is from Portugal, nearest to the southern limit of the range [120].…”
Section: Adult Maximum Sizementioning
confidence: 99%